Relative Advantage Dimensions In The Online Health Information System (SINAKES) In Semarang City of Central Java - Yuniningsih, Tri; Larasati, Endang; Lutfiana, Nurul; Hariani, Diah; Sulandari, Susi (Journal of Applied Science, Engineering, Technology, and Education, 2020)
The government is responsible for the implementation of the administration of the State, so it is demanded to improve the quality of public services so that the fulfillment of community needs can run well. One way for the government to improve the quality of public services is by creating more and more quality service. In an effort to improve public services in the field of health personnel licensing, the City of Semarang made an innovation called SINAKES Online. The purpose of this study is to analyze the relative dimensions of advantage in SINAKES Online. This study used the attributes of innovation and supporting factors and inhibitors of innovation in Rogers and Albury's public sector. The approach method that used in this study was descriptive qualitative, while data collection by observation, interview, and documentation. Data validity was done by triangulating data and sources. Data analysis was carried out by collecting data until drawing conclusions, while the determination of informants was done purposively. The results showed that in providing health personnel licensing services seen from the relative profit dimensions of innovation could be measured from economic value, social status, pleasure/satisfaction, and important components. In addition, SINAKES Online Innovation has supporting factors, namely, the desire to change for the better, the availability of facilities and infrastructure, and a supportive environment, but there are inhibiting factors; short-term budgeting and planning and dependence on high performers. The recommendations given are the need for budget allocation specifically for the development of SINAKES Online and the need for IT development training for employees by holding workshops.